Balanço social e a demonstração do valor adicionado: compromisso, sustentabilidade e transparência - Cabral, Natanael (2012)
This study aims to compare the composition of the data and the demonstration of Social Balance and Statement of Value Added to establish a discussion about contents that are presented in these financial reports. Thus, we performed a comparison between these financial statements of two major Brazilian companies listed in the ranking of companies most valuable brands in Latin America in 2011: Itaú/Unibanco and Petrobras, making a demonstrative analysis of information contained in the Social Balance of these companies, regarding their concern with social responsibility, and also demonstrate how they apply their wealth these data were extracted from Statement of Value Added of each one, in order to analyze and demonstrate the evolution or not as much data as made of the years presented. The analyzed and used datas for this study were gathered from extensive literature and academic literature on the subject and the official websites of the companies studied. Finally, it was noted that both companies use the IBASE model for preparation of the Social Balance, however, the issue of Statement of Value Added, there is no model followed, and the information contained in these approaches are differentiated. Based on this evidence, analyzes and critiques were developed involving the presented study